The Use of Selective Agar Medium to Increase the Awareness of Handwashing of Students of SD Negeri 57 Banda Aceh, Indonesia - Dewi Yunita; Saidatul Wulya; Sri Muliani; Fathurrahman Luthfi; Anggi Pratiwi; Rika Farhana (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2021)
Hand is a part of the body that contains lots of microbes. Handwashingis kind of a clean and healthy lifestyle that is aimed to reduce the number of microbes in the hand. The proper handwashing behavior should be begun to be accustomed since in elementary school, but students’ awareness is relatively low. This is alleged because they assumed that their hands look clean. In this community engagement activity on how to wash hands properly, hundred students in national primary school SD Negeri 57 Banda Aceh, Indonesia were involved from March until June 2019 and then ten students were chosen as ambassador of handwashing(ducuta). Two selective media agars were used to grow microbes from the hands of the students before and after hand washing. Several programs (secuta, mocuta, bacuta, and kacuta)were also conducted to measure the success of this activity. There was an increase in understanding the proper way of handwashing from 78% before socialization to 96% after the socialization. The results based on the handwashing activity book (bacuta) showed that 50% of the ducutahave begun to get used to washing their hands properly before eating, after going to the toilet, and after playing recommended by WHO.